Effect Of Profitability, Leverage, and Size Of Audit Public Accountant Of The Audit - Yunia Oktari; Adith Tirta Cahya (Komunitas Dosen Indonesia, 2022)
The research aims to examine the effects of profitability, leverage, and size of public accountant firm of the audit delay. The independent variables used are profitability, leverage, and size of public accountant firm. While the dependent variable used is audit delay. The research population using food and beverage companies listed in Indonesia Stock Exchange in 2014-2017. Determination of the sample using purposive sampling method and after reduces with several criteria obtained a sample of 10 sample companies. The analysis technique used in this research is linear regression analysis and processed by using SPSS program version 21. Based on the result of research showed that profitability have a significant effect on audit delay, leverage does not significant effect on audit delay , size of public accountant firm does not significant effect on audit delay, and Profitability, leverage, and size of public accountant firm simultaneously influence to audit delay.